Genetic Diversity of Seven Cattle Breeds Inferred Using Copy Number Variations - Pierce, Magretha D.; Dzama, Kennedy; Muchadeyi, Farai C. (Frontiers in Genetics, 2018)
Copy number variations (CNVs) comprise deletions, duplications and insertions found within the genome larger than 50bp in size. CNVs are thought to be primary role-players in breed formation and adaptation. South Africa boasts a diverse ecology with harsh environmental conditions and a broad spectrum of parasites and diseases that pose challenges to livestock production. This has led to the development of composite cattle breeds which combine the hardiness of Sanga breeds and the production potential of the Taurine breeds. The prevalence of CNVs within these respective breeds of cattle and the prevalence of CNV regions (CNVRs) in their diversity, adaptation and production is however not understood. This study therefore aimed to ascertain the prevalence, diversity and correlations of CNVRs within cattle breeds used in South Africa. Illumina Bovine SNP50 data and PennCNV were utilized to identify CNVRs within the genome of 287 animals from 7 cattle breeds representing Sanga, Taurine, Composite and cross breeds. 356 CNVRs of between 36kb to 4.1Mb in size were identified. The null hypothesis that one CNVR loci is independent of another was tested using the GENEPOP software. 102 and 7 of the CNVRs in the Taurine and Sanga/Composite cattle breeds demonstrated a significant (p≤0.05) association. PANTHER overrepresentation analyses of correlated CNVRs demonstrated significant enrichment of a number of biological processes, molecular functions, cellular components and protein classes. CNVR genetic variation between and within breed group was measured using phiPT which allows intra-individual variation to be suppressed and hence proved suitable for measuring binary CNVR presence/absence data. Estimate PhiPT within and between breed variance was 2.722 and 0.518 respectively. Pairwise population PhiPT values corresponded with breed type, with Taurine Holstein and Angus breeds demonstrating no between breed CNVR variation. Phylogenetic trees were drawn. CNVRs primarily clustered animals of the same breed type together. This study successfully identified, characterized and analyzed 356 CNVRs within 7 cattle breeds. CNVR correlations were evident, with many more correlations being present among the exotic Taurine breeds. CNVR genetic diversity of Sanga, Taurine and Composite breeds was ascertained with breed types exposed to similar selection pressures demonstrating analogous incidences of CNVRs.